Formulation of Risk Management Strategy for Sharia Mortgage Products during the Covid-19 Pandemic - Suherni, Siti; Isfandayani, Isfandayani; Putra, Purnama (SAN Scientific, 2024)
The COVID-19 pandemic has had a significant impact on the development of the world economy, including the banking and financial services industry. One of the financing products at Bank BTN Syariah is the Home Ownership Financing-Mortgage (Sharia KPR), where the more financing funds are channeled, of course, the greater the potential for risk. The purpose of this study was to formulate a risk management strategy for Sharia KPR products that Bank BTN Syariah KC Bekasi can use during the Covid-19 pandemic. To analyze and develop the bank strategy, we use the Grand Strategy Matrix method by blending internal and external factors, where the analysis and strategy selection process is divided into three stages: Input stage, matching stage, and Decision stage. The results of the study showed that several internal and external factors occur in Bank BTN Sharia KC Bekasi that affect the development of Sharia KPR products; Bank BTN applies risk management based on the 5C principle to minimize the occurrence of risks that may occur. Managerial implications of this research are credit risk management, management, increased risk monitoring, effective communication, product innovation, conducting education and training, and Sharia compliance.